Evaluación de la composición química y actividad antileishmanial de cuatro muestras de propóleos ecuatorianos de abejas sin aguijón. - Plaza Juárez, Cristian Manuel (2017)
Propolis is a product of mixed origin (animal and vegetable) that make bees from vegetable exudates and wax produced by young workers, which incorporate their saliva. It is a resinous material of variable color that has been widely used since antiquity by man for medicinal purposes and for embalming corpses. In this work the chemical composition and antileishmanial activity of four samples of Ecuadorian propolis produced by stingless bees were evaluated by chromatographic, spectroscopic and in vitro assays. The samples under study come from three regions of Ecuador, including the Costa, Sierra and Oriente areas. The provinces represented in this study were El Oro, Loja, Pastaza and Sucumbíos. For the extraction of the chemical components present in the propolis samples, the maceration method was used using ethyl alcohol for 7 days with solvent replacement on the third and fifth day. The obtained ethanolic extracts were filtered, collected and concentrated to dryness under reduced pressure using a Buchi Rotoevaporator, applying a temperature no greater than 30 ° C. All crude extracts were analyzed by thin layer chromatography using silica gel 60 GF254, different mobile phases and development systems to obtain a preliminary fingerprint and compare them to each other. Gas chromatography coupled to mass spectrometry was also used for the structural characterization of the organic compounds present in the extracts. The equipment used was an Agilent 6890 gas chromatograph coupled to a 5973N mass spectrometer and the samples were subjected to derivatization to obtain the corresponding trimethylsilyl ethers. Likewise, the antiparasitic activity of the extracts obtained was evaluated against L. amazonensis promastigotes and the toxicity was determined against BALB / c mouse peritoneal macrophages. Preliminary studies using thin layer chromatography allowed to detect the similarity of the extracts evaluated as to the possible presence of compound of triterpene nature and its little or no ability to sequester the stable radical DPPH. The best results were obtained by using dichloromethane as the mobile phase and the sulfuric acid / vanillin combination as the developer. In gas chromatography coupled to mass spectrometry, all samples revealed complex chromatograms with a total of 46 compounds identified where sugars, alcohols, fatty acids and triterpenes are included as main identified components. The triterpenes α and β-amirine were the compounds that showed the most distribution in the samples, although it was also appreciated the presence of cycloartanol, lanosterol and other compounds of diverse nature could not be identified. The results of the gas chromatography showed correspondence with the results obtained in the preliminary studies of thin layer chromatography by CCD. In the antiparasitic study samples 1S (Loja), 3S (El Oro), 4S (Pastaza) did not reveal activity against L. amazonensis; the 2S sample (Sucumbíos) showed the highest activity with an inhibitory concentration 50 (IC50) of 73.6 ± 1.5 ug / mL. In the cytotoxic evaluation all extracts showed toxicity to mouse macrophages and selectivity indexes were less than 1.